2015
DOI: 10.1016/j.jfma.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for central venous access port-related infection in Chinese cancer patients

Abstract: Infection remains to be a challenging issue for totally implantable central venous ports. Implementation of an insertion bundle for the prevention of central line-associated bloodstream infections is warranted, especially for those patients with hematological and head and neck cancers, as well as for patients receiving chemotherapy in the metastatic settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 22 publications
(13 reference statements)
5
31
1
1
Order By: Relevance
“…Central line-associated bloodstream infections (CLABSIs), the majority related with the use of the central venous catheter (CVC) [6,7], are the most important complications in critical care [810] and in cancer settings [11,12]. In particular, in cancer settings, several risk factors have been identified for CLABSIs in patients who undergo chemotherapy such as, for example, a prolonged duration of catheterization, microbial colonization at the insertion site and of the catheter hub, and inadequate care/maintenance of the CVC after insertion [1315].…”
Section: Introductionmentioning
confidence: 99%
“…Central line-associated bloodstream infections (CLABSIs), the majority related with the use of the central venous catheter (CVC) [6,7], are the most important complications in critical care [810] and in cancer settings [11,12]. In particular, in cancer settings, several risk factors have been identified for CLABSIs in patients who undergo chemotherapy such as, for example, a prolonged duration of catheterization, microbial colonization at the insertion site and of the catheter hub, and inadequate care/maintenance of the CVC after insertion [1315].…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that colonization of the skin was more prominent in subclavian vein insertions than in the forearm region. 13,2015 Of the 1391 patients evaluated, 62% were male and 38% female, with a mean age of 59.8 years. A total of 249 patients were included in the study, with a mean age of 62 years and female prevalence (60%).…”
Section: 2016mentioning
confidence: 99%
“…12, The study, which (n = 1391). 13 The data referring to the results and conclusions of the studies analyzed were compiled in figure 3.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations